Beamspace Channel Estimation With Beam Squint Effect for the Millimeter-Wave MIMO-OFDM Systems - Xiaohao Mo (IEEE, 2021)
In this paper, we investigate two novel beamspace channel estimation schemes for millimeter-wave MIMO-OFDM systems relying on a uniform linear antenna array. Based on the sparse nature of the beamspace channel, compressive sensing-based methods can be adopted. Most of the existing wideband beamspace channel estimation schemes take the common support assumption that the support of all sub-carriers from a single path component keeps unchanged. However, due to the beam squint effect caused by time delays among different antennas, this assumption is no longer satisfied. Based on the above, we analyze the frequency-dependent sparse structure of the beamspace channel due to beam squint and propose the block simultaneous orthogonal matching pursuit algorithm where support is jointly estimated by using beamspace windows. Moreover, considering the power focusing effect of beam squint, we propose the two-stage beamspace channel estimation scheme, where the first stage is for the angle of arrival estimation, and the second stage is for updating path gain to reconstruct the beamspace channel. Simulation results demonstrate that proposed schemes can estimate the channel under the beam squint effect with high accuracy but low pilot overheads.